Advances in Ergonomics in Design Proceedings of the AHFE 2016 International Conference on Ergonomics in Design, July 27-31, 2016, Walt Disney World®, Florida, USA - Rebelo, Francisco; Soares, Marcelo (Advances in Intelligent Systems and Computing, 2016)
This book provides readers with a timely snapshot of ergonomics research and methods applied to design, development, prototyping, as well as evaluation, training and manufacturing of products, systems and services. It includes theoretical contributions, case studies, and reports on technical interventions. The book covers a wide range of topics in ergonomic design, such as ecological design, educational and game design, cultural and ethical aspects in design, user research and human-computer-interaction in design, as well as design for accessibility and extreme environments, and many others. The book gives special emphasis to new technologies such as virtual reality, state-of-the-art methodologies in information design, and human-computer interfaces. Based on the AHFE 2016 International Conference on Ergonomics in Design, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, this book represents a timely guide for both researcher and design practitioners, including industrial designers, human-computer interaction and user experience researchers, production engineers and applied psychologists.